1997
DOI: 10.1111/j.1502-3931.1997.tb00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of spiral growth in planorbid gastropods

Abstract: Extensive experimentation has been performed on the planorbid Planorbarius metidjensis in order to determine which mechanism allows the snail to coil its shell regularly. Individuals of this species, like all Planorbidae, are permanently active and secrete their shells while crawling on the substrate. Experiments consisted of attaching weights to either side of the shell (which is carried almost vertically) in an umbilical position; these weights cause the shell to fall towards the substrate on the loaded side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The comparison of shell shape between and within different clades of mollusks can be informative with regards to the basic rules of accretionary growth. Common rules of growth could underlie the morphogenesis of the shell and its evolution in ammonoids and gastropods (Bucher 1997;Bucher and Guex 1990;Bucher et al 1996;Checa and Jimenez-Jimenez 1997;Checa et al 1998Checa et al , 2002. Evidences come from the comparison of intraspecific and/or interspecific patterns of covariation among shell characters (Westermann 1966;Morita 1991aMorita , b, 2003Dagys and Weitschat 1993;Checa et al 1996;Hammer and Bucher 2005a), from the description of changes occurring at maturity in different species or clades (Thompson 1917;Burnaby 1966;Bucher 1997;Chirat et al 2008), and from the analysis of teratological shells in response to injuries (Thompson 1917;Guex 1967Guex , 1968Bayer 1970;Landman and Waage 1986;Bond and Saunders 1989;Hammer and Bucher 2005b) or to change in living conditions (Linsley 1977;Checa and Jimenez-Jimenez 1997;Checa et al 2002).…”
Section: Molar Proportionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison of shell shape between and within different clades of mollusks can be informative with regards to the basic rules of accretionary growth. Common rules of growth could underlie the morphogenesis of the shell and its evolution in ammonoids and gastropods (Bucher 1997;Bucher and Guex 1990;Bucher et al 1996;Checa and Jimenez-Jimenez 1997;Checa et al 1998Checa et al , 2002. Evidences come from the comparison of intraspecific and/or interspecific patterns of covariation among shell characters (Westermann 1966;Morita 1991aMorita , b, 2003Dagys and Weitschat 1993;Checa et al 1996;Hammer and Bucher 2005a), from the description of changes occurring at maturity in different species or clades (Thompson 1917;Burnaby 1966;Bucher 1997;Chirat et al 2008), and from the analysis of teratological shells in response to injuries (Thompson 1917;Guex 1967Guex , 1968Bayer 1970;Landman and Waage 1986;Bond and Saunders 1989;Hammer and Bucher 2005b) or to change in living conditions (Linsley 1977;Checa and Jimenez-Jimenez 1997;Checa et al 2002).…”
Section: Molar Proportionsmentioning
confidence: 99%
“…Some studies highlighted the generic rules underlying the morphogenesis of the molluscan shell, using either geometrical (Thompson 1917;Raup 1961;Raup and Michelson 1965;Okamoto 1988a, b;Illert 1990;Savazzi 1990;Rice 1998;Ubukata 2003;Hammer and Bucher 2005b;Urdy et al 2010a, b), mechanical (Morita 1991a, b;Morita 1993;Vermeij 2002;Hammer and Bucher 2005a), or chemical models (Hammer and Bucher 1999;Guex et al 2003). Some other studies laid emphasis on the role of life orientation in the determination of growth direction (Linsley 1977(Linsley , 1978Checa and Jimenez-Jimenez 1997;Checa et al 2002). Others suggested that the preceding whorl played a role in the regulation of coiling (Hutchinson 1989;Checa et al 1998;Morita 2003).…”
Section: Molar Proportionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, models, which would apply only to ammonoids-such as those related to septa formation (i.e. Bayer 1977;García-Ruiz et al 1990;Checa and García-Ruiz 1996;Pérez-Claros et al 2007; Klug and Hoffmann (2015))-will not be discussed here.…”
Section: Introductionmentioning
confidence: 97%
“…Such models have expanded beyond the reaction–diffusion systems of Meinhardt (Meinhardt, , , Meinhardt & Klingler, ) to include neurosecretory models (Boettiger, Ermentrout, & Oster, ; Ermentrout, Campbell, & Oster, ; Saleuddin & Kunigelis, ) and the “road‐holding” hypothesis, which posits that shell growth is guided by spatial feedback from shell previously deposited one revolution earlier (Hammer & Bucher, ; Hutchinson, ). Although the growth of shell sculpture has been observed in many taxa (Berry, ; Gostan, ; Illert, ; Inaba, ; Laxton, ; Liew, Kok, Schilthuizen, & Urdy, ; MacGinitie & MacGinitie, ; Spight, Birkeland, & Lyons, ; Spight & Lyons, ), experimental studies of how different types of sculpture are produced are rare (Checa & Jiménez‐Jiménez, ; Checa, Jiménez‐Jiménez, & Rivas, ; Webster & Palmer, , ). Yet to distinguish among various models of sculpture growth, experimental studies are essential.…”
Section: Introductionmentioning
confidence: 99%